Differences in the risk of stroke, bleeding events, and mortality between female and male patients with atrial fibrillation during warfarin therapy. Issue 1 (21st July 2018) - Penttilä, Tero; Lehto, Mika; Niiranen, Jussi; Mehtälä, Juha; Khanfir, Houssem; Lassila, Riitta; Raatikainen, Pekka
Abstract: Aims: Females with atrial fibrillation (AF) have been suggested to carry a higher risk for thromboembolic events than males. We compared the residual risk of stroke, bleeding events, and cardiovascular and all-cause mortality among female and male AF patients taking warfarin. Methods and results: Data from several nationwide registries and laboratory databases were linked with the civil registration number of the patients. A total of 54 568 patients with data on the quality of warfarin treatment (time in therapeutic range) 60 days prior to the events were included (TTR60). Gender differences in the endpoints were reported for the whole population, pre-specified age groups, and different TTR60 groups. During the 3.2 ± 1.6 years follow-up, there were no differences in the adjusted risk of stroke [hazard ratio (HR) 0.97, 95% confidence interval (CI) 0.91–1.03, P = 0.304] between the genders. Cardiovascular mortality (HR 0.82, 95% CI 0.78–0.88, P < 0.001) and all-cause mortality (HR 0.79, 95% CI 0.75–0.83, P < 0.001) were lower in women when compared with men. There were no differences in the risk of stroke, cardiovascular mortality, and all-cause mortality between the genders in the TTR60 categories except for those with TTR60 <50%. Bleeding events were less frequent in females (HR 0.52, 95% CI 0.49–0.56, P < 0.001). Conclusion: There were no differences in the risk of stroke between female and male AF patients taking warfarin. Cardiovascular mortality, all-cause mortality, and risk of bleeding events were lower in females. Hence, female gender was not a risk marker for adverse outcomes in AF patients with proper warfarin therapy.